2005
DOI: 10.1159/000088623
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide Reduces Superoxide and Peroxynitrite Anion Chemiluminescence during Human Neutrophil Bursts

Abstract: Many lung disorders are characterized by airway inflammation involving the recruitment of inflammatory cells, and leading to the release of oxidant and inflammatory mediators. The overproduction of superoxide anion (O2DELETE) and nitric oxide (NO) during the respiratory bursts of neutrophils leads to production of peroxynitrite, a highly damaging oxidant with an important role in the inflammatory loop causing airway hyper-reactivity in respiratory diseases like asthma. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…respiratory burst) (127). As CXCL1 had a down-regulating effect only when combined with formoterol and/or budesonide, it is interesting that both salmeterol and budesonide have been shown to reduce the respiratory burst in neutrophils (128,129).…”
Section: Discussionmentioning
confidence: 99%
“…respiratory burst) (127). As CXCL1 had a down-regulating effect only when combined with formoterol and/or budesonide, it is interesting that both salmeterol and budesonide have been shown to reduce the respiratory burst in neutrophils (128,129).…”
Section: Discussionmentioning
confidence: 99%
“…30 Some other studies also showed that the high lipophilicity of BUD, the high solubility of BUD in PS, and its high affinity with the lung tissue made BUD a better choice in terms of the anti-inflammatory, anti-oxidative, and pulmonary edema-reducing effects of glucocorticoids. [31][32][33] It should be noted that, for intratracheal administration of BUD using exogenous surfactant as a carrier, the effect of BUD on the surface activity of surfactant depend on the selection of the surfactant preparation, as well as their mixing ratio. 34,35 If Infasurf, a cholesterolcontaining surfactant preparation, is used to deliver BUD at a concentration higher than 1%, BUD may significantly compromise its surface activity.…”
Section: Milos Et Al Found Quite Recently That High Tidal Volume Ventmentioning
confidence: 99%
“…BUD and erdosteine (through Met I) are both active in reducing the release of O 2 -ؒ , NO and ONOO - [23,30,31] , and are usually administered in patients with respiratory diseases. PMNs are major sources of ROS and peroxynitrite production, but the effects of combining Met I and BUD have not yet been analyzed at this level.…”
Section: Introductionmentioning
confidence: 99%